Causes of depressive disorders and their degree and severity among high school students - Zając, Anna; Dobko, Katarzyna; Frącz, Gabriela; Glac, Agata; Kuliga, Klaudia; Musz, Kinga; Sejnowska, Natalia; Socha, Agnieszka; Surowiec, Agata; Śnieżek, Kinga (Journal of Education, Health and Sport, 2023)
Introduction: Depressive disorders are common in children and adolescents, but often go undiagnosed. They are associated with serious consequences, as well as with serious impairments both in terms of personal and social life, increasing the risk of suicide and psychoactive substance abuse. Objective: The aim of the study was to analyze the most common factors causing depressive disorders and to assess their frequency and severity among adolescents. Materials and methods:The study was conducted in one of the secondary schools in Krosno. 316 students (245 girls, 71 boys) aged 15 to 19 participated in the study. The results of 27 questions on depressive disorders were obtained using an anonymous online questionnaire. Results: Among 316 students, as many as 40.5% do not know whether they suffer from depressive disorders, while 12% are sure of it, of which 71% have started treatment. However, sadness and depression as well as loss of interest and pleasure from doing favorite activities lasting 2 weeks or more, as well as a sense of worthlessness and lower self-esteem reach over 27% of students. The study shows that 15% of students may be undiagnosed. Suicidal thoughts occur in 44.9% of the respondents. 6.3% of students have attempted suicide and 2.8% want to take their own lives. Conclusions: Depressive disorders are a common problem among hight school studnets. The most common disorders coexisting with depression in the examined adolescents were eating disorders. Increased awareness of depression symptoms among adolescents, parents, school psychologist and family doctor is a key element for diagnosis and therapy.